Tussen droom en werklikheid : die voorstelling van die sakewêreld in die oeuvre van Willem Elsschot - Janse van Rensburg, Christa Irene Marie (Afrikaans and Netherlandic Studies, 2017)
This study investigates the representation of the business world in the oeuvre of Willem Elsschot. Firstly Elsschot as businessman levels criticism at a capitalistic economic system of which he himself was part. An ambivalence, namely humanitarianism versus profit, emerge through the sober style in which Elsschot's writes. Style was very important to Elsschot. Secondly, Elsschot illuminates the ideological tension between capitalism and socialism present in his oeuvre. Thirdly Elsschot provides the reader with insight into his fiction by incorporating in a realistic manner the historical, economic and social background of the society of his time. His representation of the business world implies social commentary on the civilian life of which he was part and from which he never really escaped. He seeks through his portrayal of capitalism a more moral society where the weak would no longer be seen as objects through whose usefulness more profit could be gained for capitalism. In this way he tacitly supports socialistic notions without ever actually practising or choosing socialist party politics. Fourthly, the autobiographical aspect of Elsschot's representation of the business world deserves mention. Although the characters in his oeuvre refer back to historical figures, and he draws from his own experience to create the business world about which he writes, it would be dangerous to assume that his writing is merely a realistic representation of Elsschot's own life. Fifthly, Elsschot examines the church as an instrument in the hands of capitalism. His representation of the church serves as criticism against the Roman Catholic Church which dominated many facets of Belgian society. Elsschot considers it as hypocracy when the church and the business world are seen to behave similarly. Elsschot uses different techniques to describe the business world. Style, being the first one captures Elsschot's choice of words, his overaccentuation and his use of language. Characterization is the second technique that requires consideration. Elsschot's characters act in pairs, an outward representation of the duality, humanitarianism is profit making, ("droom versus werklikheid") that is present in his characters. Even Elsschot as successful businessman himself, Alfons de Ridder, experiences this conflict and writes under the pseudonym Willem Elsschot. The last technique that contributes to the description of the business world is the evocation of unusual worlds with which to compare the real business world. The juxtaposition of everyday occurrences with biblical events for example strengthens the irony and humour in his style. Finally, this study determines Elsschot's motivation in representing the business world in the way that he does; to what extent he is influenced by the history, the ideologies and the society of his time and to what extent he was influenced by the conventions of his time. Although Elsschot has been dead for 38 years, the vitality and realism in his oeuvre are still strong and he still has many readers.